Bandoeng Tempo Doeloe: Perubahan Sosial di Bandung Dalam Masa Pendudukan Jepang Tahun 1942-1945 - Devi Olivia (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Bandung is one of the regions in West Java that has been established for a very long time. Various periods have been passed by the Bandung area ranging from ancient times, royal periods, colonial periods, movement periods, to the present day. In line with the passage of time that Bandung has passed, various social changes have arisen that were felt by the people of Bandung at that time. One of the social changes that was felt by the people of Bandung was during the colonial period until the independence period. This is what moved researchers to conduct research with the aim of researching how much change and impact the people of Bandung felt at that time. The methodology used in this study is literature studies such as books, articles, and so on. These sources are related to or in line with the situation or condition of the people of Bandung during the transition period of colonialism and independence. The result of this study is how Bandung is depicted during the Netherlands occupation, the Japanese occupation period, and the Independence period in terms of social changes and their impact on society.